Roles and Molecular Mechanisms of Physical Exercise in Sepsis Treatment - Wu, You; Guo, Xiaofeng; Peng, Yuliang; Fang, Zongping; Zhang, Xijing (Frontiers in Physiology, 2022)
Physical exercise is a planned, purposeful action to keep a healthy lifestyle and improve physical fitness. Physical exercise has been widely used as a non-pharmacological approach to preventing and improving a wide range of diseases, including cardiovascular disease, cancer, metabolic disease, and neurodegenerative disease. However, the effects of physical exercise on sepsis have not been summarized until now. In this review, we discuss the effects of physical exercise on multiple organ functions and the short- and long-time outcomes of sepsis. Furthermore, the molecular mechanisms underlying the protective effects of physical exercise on sepsis are discussed. In conclusion, we consider that physical exercise may be a beneficial and non-pharmacological alternative for the treatment of sepsis.